Kompetensi Absolut dalam Badan Arbitrase Nasional Indonesia dalam Penyelesaian Sengketa Berdasarkan Perjanjian Penyaluran Tenaga Listrik (Studi Putusan Nomor: 681/Pdt.G/2019/Pn.Jkt.Sel) - Agustinus Alva, Jonathan (UNES Law Review, 2023)
Arbitration is one way between parties to resolve an arbitration based on an agreement made by the parties. Settlements using arbitration are generally made by the parties by inserting an arbitration clause into an agreement to resolve a settlement outside of court for the parties. However, in practice, the settlement for the parties is still carried out in court, which should refer to the contents of the agreement which contains an arbitration clause, then the settlement of the parties must be carried out through arbitration in accordance with the contents of the agreement agreed to by the parties, which is binding on the parties. party. So this research raises two main problems, namely how the provisions for arbitration settlement are based on the arbitration clause agreement regarding the Pactum de Compromittendo in Indonesia. Based on Law 30 of 1999 concerning arbitration and alternative settlements and what are the legal provisions in Indonesia regarding absolute competence in cases of arbitration clause agreements in Indonesia. To answer this problem, normative juridical research was carried out on study decision number: 681/PDT.G/2019/PN.JKT.SEL. Data processing is carried out qualitatively, while conclusions are drawn based on deductive logic. Based on analysis of study decision number: 681/PDT.G/2019/PN.JKT.SEL. It is known that there are agreements that contain an arbitration clause made by the parties, but the settlement is resolved through court and then the court still accepts and decides on the settlement, even though the agreement made by the parties contains an arbitration clause.